Human-existence probability of the Aurignacian techno-complex under extreme climate conditions. (1st July 2021) - Shao, Yaping; Limberg, Heiko; Klein, Konstantin; Wegener, Christian; Schmidt, Isabell; Weniger, Gerd-Christian; Hense, Andreas; Rostami, Masoud
Abstract: The Aurignacian occurred in the middle of the Last Glacial Period, in which climate underwent major changes on millennial time scales, highlighted by the Greenland interstadial and stadial periods. Here we investigate how climate change influenced the Aurignacian human dispersal in Europe and search for answers to several highly-debated questions in the Archaeology and Paleoanthropology. We use a global climate model to simulate the prototypical stadial and interstadial climate conditions and develop a human-existence potential (HEP) model to compute the probability of human existence by combining the climate data with archaeological site data. Using the HEP model, we reconstruct the patterns of human-existence probability and provide a pan-European overview of the Aurignacian human dispersal. The model results suggest that climate change significantly influences human dispersal, but there is evidence of human adaptation to climate. The Aurignacian dispersal is likely achieved in alternating modes of expansion and contraction. In comparison to interstadial times, human-existence probability in stadial times is largely reduced, but hot-spots exist in the climate shadows of large topographic features. Highlights: Human-Existence Potential (HEP) allows an overview of Pan-European human dispersal in Aurignacian. Estimates of human-existence probability, range of human dispersal and regional variability. Climate influenced human dispersal, but evidence for human adaptation exists. In stadial times, human-existence hot-spots in climate shadows of large topographic features. Aurignacian expansion achieved in alternating modes of expansion and contraction.